(untitled) (Fiep Bulletin - online, 2014)
The present research was carried through in the Pertaining to school Group Guilhermina Bucheller Woman in the period of August the November of 2006, searching to understand as the motor capacity can be worked flexibility that is understood by Weineck (1999) as the capacity to carry through a movement with the maximum amplitude to articulate, in the activities of the lessons of Physical Education. We carry through interviews with the professors in order to know as the activities with its pupils were developed. In the sequence we organize the interventions to be carried through. For this organization the activities had been based in what Dantas considers (1989) making possible to promote to the educandos the appropriation of the knowledge on the motor capacity flexibility and its different manifestations in the context of the pertaining to school Physical Education. Ahead of the organization of the lesson plans didactic metodológica based in the progressive perspective was established aa. With the agreement of that the progressive perspective detaches the motricidades human beings and that its objective is to diagnosis imperfections in the performance, it was possible to perceive in the end of the interventions that the considered objectives had been reached, therefore the pupils had learned because that they were executing the activities, and not simply executing them mecanicamente. As future professional of the area, I could perceive that the allonge when worked of form to the pupil to know because to execute always it finishes it being carried through for same with more envolvement and efficiency.